Audit committee expertise on audit fees / Nurul Azlin Azmi, Fazrul Hanim Abd Sata and Norhidayah Abdullah - Azmi, Nurul Azlin; Abd Sata, Fazrul Hanim; Abdullah, Norhidayah (2012)
This study extends the previous researcher on the audit fees by examining the association between audit committee characteristic and audit fees. The study specifically investigates the impact of the Malaysian Code of Corporate Governance 2007 on the audit committee characteristics (size, independence, meeting, expertise and training). This study examines the effect of audit committee expertise by including the number of financial-related training attended by directors as a tool to measure the expertise of the audit committees. Besides that, an experience of the audit committee members are strengthening for those who have more than three year experience in accounting and financing as well as in professional bodies. This finding indicates audit fees are significantly and negatively associated with audit committee size and audit committee training. Thus, size and training of audit committee could give an impact to the lower of audit fees. However, an audit fee is significantly and has positively association with audit committee expertise. Expertise of the audit committee has lead to higher audit fees due to their effectiveness in discharging their roles that allow members to demand additional assurance and higher audit quality. This study contributes to the growing of literature by demonstrating the significant of the relevant financial-related training that will give effect to the expertise of audit committee members. The findings are also relevant to the policy-maker and to practitioners in term of best disclosure of the director's training in annual report.